Construction on exact solutions of diffusion equation - Barannyk, Anatoliy; Yuryk, Ivan (My University, 2004)
New extended classes of exact solutions of a nonlinear diffusion equation are constructed.
Keywords: transformation gole-hopf; exact solutions; точні розвязки; підстановки коула-хопфа; точные решения; подстановки коула-хопфа; кафедра вищої математики імені проф. Можара В. І.